2020
DOI: 10.21831/reid.v6i1.21996
|View full text |Cite
|
Sign up to set email alerts
|

Developing instruments for measuring the level of early childhood development

Abstract: The aims of the study were to: (1) develop a set of instruments to measure the level of early childhood development (kindergarten group B), and (2) assess the quality of the developed instruments. This study is developmental research. The samples of the study were the students of kindergarten group B. The developed instrument was a set of questionnaires. Instrument testing was carried out in three stages with the number of subjects increased on each stage. The validity analysis of the questionnaire used confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…According to Pressman & Bruce (2014: 9) mobile apps or mobile applications are computer programs that are specifically made to run on mobile phone or tablet handheld devices [5]. Applications also have the meaning of problem solving that uses one of the application data processing techniques which usually races on a computing or data processing that is expected [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Pressman & Bruce (2014: 9) mobile apps or mobile applications are computer programs that are specifically made to run on mobile phone or tablet handheld devices [5]. Applications also have the meaning of problem solving that uses one of the application data processing techniques which usually races on a computing or data processing that is expected [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research by Hermawati (2007) in a children daycare in Beringharjo, Yogyakarta, found two drawbacks of the input variables, namely, the teacher's educational background and caregiver qualifications that are not relevant to the tasks. In the process variables, the problem is the immeasurability of mentoring by a caregiver.…”
Section: Introductionmentioning
confidence: 99%